Investigating the effects of the lithium-mimetic drug, ebselen, on emotional processing and brain neurochemistry in patients with medication-resistant depression - Ramli, FF (2024)
Background: Inadequate responses to standard antidepressant treatment is a challenging condition with complicated management. Augmentation with lithium is thought to be effective, but adverse effects limit its widespread use. Ebselen is a lithium-mimetic drug with similar mechanisms of action to lithium, in particular an ability to inhibit the enzyme, inositol monophosphatase (IMPase). Studies in healthy volunteers found that ebselen has antidepressant potential as assessed using emotional processing and is well tolerated.